Molecular modeling of Ag4 cluster formation. Issue 1 (3rd May 2021) - Kytsya, Andriy; Bazylyak, Liliya; Pasternak, Olena; Turovskii, Mykola
Abstract: Nucleation is the main process which affects on the characteristics of the formed metal nanoparticles. At the same time the mechanism of homogeneous nucleation of metal particles in solutions are still debatable. There are two contrary points of view which briefly may be presented as "Instantaneous" and "Continuous". Instantaneous nucleation postulated by classical nucleation theory (CNT) means formation of nuclei as a result of supersaturation of solution via set of equilibrium reactions (on the whole nA⇔An ) but Continuous nucleation implies step-by-step irreversible addition of monomer to formation of nuclei and/or nanoparticle (A→A2 →…→An ). Using DFT calculations the thermodynamic parameters of all possible reactions leading to formation of Ag4 cluster which may be considered as intermediate in the nucleation process have been estimated. It was found that formation of Ag4 is thermodynamically possible via both of mechanisms. At the same time it was noted that addition of Ag + to silver cluster is more preferred than association of uncharged particles. Taking into account the much higher concentration of silver ions compared to silver atoms this fact may indicate on the preference of stepwise mechanism of nucleation of metal nanoparticles in real solutions.